Recovering and updating senses of authority: a historical trajectory - Torres, Maria Carmen Euler; Castro, Lucia Rabello de (Paidéia (Ribeirão Preto), 2009)
Study based on the evidence that children and adults lack references on how they deal with each other, which has being showed by the young generation through confronting attitudes toward adults. When the historical route of authority is considered, one perceives it is not tied to one meaning only but takes different contours. This article aims to discuss the relations between authority and hierarchy, authority and power, and authority and foundation, which help to understand that what used to be showed as "the truth" does not give account of the imperfections of current human relationships, appointing other possible constructions of the authority sense.